Doing qualitative research online - Salmons, Janet 1952- (SAGE, 2016)
Qualitative researchers can now connect with participants online to collect deep, rich data and generate new understandings of contemporary research phenomena. Doing Qualitative Research Online gives students and researchers the practical and scholarly foundations needed to gain digital research literacies essential for designing and conducting studies based on qualitative data collected online. The book will take a broad view of methodologies, methods and ethics, covering: ethical issues in research design and ethical relationships with participants; designing online qualitative studies; collecting qualitative data online through interviews, observations, participatory and arts-based research and a wide range of posts and documents; analyzing data and reporting findings. Written by a scholar-practitioner in e-learning and online academia with 15 years experience, this book will help all those new to online research by providing a range of examples and illustrations from published research. The text and accompanying materials will offer discussion and assignment ideas for ease of adoption.